Dammarane-type triterpenoid saponins from the flower buds of Panax pseudoginseng with cytotoxic activity. Issue 17 (1st September 2022) - Hanh, Tran Thi Hong; Cham, Pham Thi; Anh, Do Hoang; Cuong, Nguyen The; Trung, Nguyen Quang; Quang, Tran Hong; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Minh, Chau Van
Abstract: Phytochemical investigation of a methanol extract of Panax pseudoginseng flower buds resulted in the isolation of 22 dammarane-type triterpenoid saponins, including three new compounds, pseudoginsenosides A-C (1 -3 ), and 19 known analogs. Their chemical structures were identified by the comprehensive spectroscopic methods, including 1 D and 2 D NMR and mass spectra. In addition, their cytotoxic effects toward three human carcinoma cell lines, including liver (HepG2), breast (MCF7), and lung (A549) were also evaluated. Graphical Abstract: UF0001